Schimke immuno-osseous dysplasia: case report and review of 25 patients. Issue 10 (1st October 1999) - Saraiva, Jorge M; Dinis, Alexandra; Resende, Cristina; Faria, Emília; Gomes, Clara; Correia, A Jorge; Gil, Júlia; da Fonseca, Nicolau
Abstract : Immuno-osseous dysplasia is characterised by spondyloepiphyseal dysplasia, lymphopenia with defective cellular immunity, and progressive renal disease. We describe a patient with a severe form of the disease, review the features of another 24 patients, and discuss the previous classification. The differences between the two groups are not striking, and although similarities are greater between affected sibs, the same diagnosis of Schimke immuno-osseous dysplasia should apply to them all. The aetiology and physiopathology of this rare osteochondrodysplasia of presumed autosomal recessive inheritance remain unknown.